LncGPR107 drives the self-renewal of liver tumor initiating cells and liver tumorigenesis through GPR107-dependent manner - Guanqun Huang; Hui Jiang; Ye Lin; Wuzheng Xia; Yuanwei Luo; Yanpeng Wu; Weilong Cai; Xinke Zhou; Xianhan Jiang (Journal of Experimental & Clinical Cancer Research, 2018)
Abstract Background With self-renewal and differentiation properties, liver tumor initiating cells (TICs) are the reasons for tumor initiation, metastasis and drug resistance. G protein coupled receptors (GPCR) are critical modulators in many physiological and pathological processes. While, their roles in liver TICs are unknown. Methods An unbiased screening was performed using online-available data dataset. Liver TICs were sorted by FACS with surface marker CD133, or enriched by oncosphere formation. TIC self-renewal was examined by oncosphere formation and tumor initiation assay. Loss of function and gain of function assays were performed to examine the role of lncRNA. RNA pulldown, RNA immunoprecipitation, ChIP, western blot and double FISH were used explore the molecular mechanism of lncRNA. Results We performed an unbiased screening for GPCR expression in liver cancers, and found GPR107 was the most highly expressed GPCR in liver cancer and liver TICs. GPR107 was essential for the self-renewal of liver TICs. The expression of GPR107 was regulated by a long noncoding RNA lncGPR107. LncGPR107 was also highly expressed in liver cancers and liver TICs. LncGPR107 drove the self-renewal of liver TICs through GPR107. Moreover, lncGPR107 recruited SRCAP complex to GPR107 promoter to drive its transcriptional activation. LncGPR107 depletion inhibited the binding of SRCAP complex and GPR107 promoter and subsequent GPR107 expression. Moreover, LncGPR107-SRCAP-GPR107 can be targeted for liver TIC elimination. Conclusion GPR107 was the most highly expressed GPCR in liver cancer and liver TICs. LncGPR107 participated in the transcriptional regulation of GPR107 in cis, through recruiting SRCAP remodeling complex to GPR107 promoter. This work revealed the important role of GPCR signaling in liver TIC self-renewal and added a new layer for liver TIC and GPCR regulation.